Current Trends in Implantable Left Ventricular Assist Devices - Jens Garbade; Hartmuth B. Bittner; Markus J. Barten; Friedrich-Wilhelm Mohr (Cardiology Research and Practice)
The shortage of appropriate donor organs and the expanding pool of patients waiting for heart transplantation have led to growing interest in alternative strategies, particularly in mechanical circulatory support. Improved results and the increased applicability and durability with left ventricular assist devices (LVADs) have enhanced this treatment option available for end-stage heart failure patients. Moreover, outcome with newer pumps have evolved to destination therapy for such patients. Currently, results using nonpulsatile continuous flow pumps document the evolution in outcomes following destination therapy achieved subsequent to the landmark Randomized Evaluation of Mechanical Assistance for the Treatment of Congestive Heart Failure Trial (REMATCH), as well as the outcome of pulsatile designed second-generation LVADs. This review describes the currently available types of LVADs, their clinical use and outcomes, and focuses on the patient selection process.